Evaluation of cyclic efficiency of multilayer desiccant bed column - Prueksa Sawardsuk; Jiraporn Sripinyowanich Jongyingcharoen; Ekkapong Cheevitsopon (My University, 2020)
The main objective was to evaluate cyclic efficiency of a multilayer desiccant bed column. The experimental setup consisted of an air humidifier unit, a heating unit for regeneration, and the desiccant bed column with 15 layers. An airflow rate of 2.4 m 3 /min with the humidity ratio of 20 g water/kg dry air was used in this study. The results showed that the highest dehumidification rate of 21 g water/min was found at the beginning of the dehumidification process. During the regeneration process, the highest regeneration rate was 39 g water/min when regenerating the desiccant at a temperature of 90°C. For cyclic operation process, the cyclic efficiencies were 11% and 7% at the regeneration temperatures of 70°C and 90°C, respectively. The cyclic efficiency was dependent on the regeneration temperature.
Keywords: Adsorption and Cooling Systems